Упростить:

а) (cos^2 a-ctg^2 a)/(tg^2 a-sin^2 a)=

б) (1+tg a+tg^2 a)/(1+ctg a+ctg^2 a)=

в) tg a/(1-tg^2 a) * (ctg^2 a - 1)/ctg a)=

Спасибо заранее..

1

Ответы и объяснения

2013-01-19T13:52:16+04:00

а) (cos^2 a-ctg^2 a)/(tg^2 a-sin^2 a)={cos^2a(1-1/sin^2a)}/{sin^2a(1/cos^2a-1)}={cos^2a/sin^2a}*{(sin^2a-1)/sin^2a}/{(1-cos^2a)/cos^2a}=ctg^2a*{-cos^2a/sin^2a}/{sin^2a/cos^2a}=ctg^2a*-ctg^2a/tg^2a==ctg^4a*ctg^2a==ctg^6a

извините некогда

 в) 

в) tg a/(1-tg^2 a) * (ctg^2 a - 1)/ctg a)=tga/{1-sin^2a/cos^2a}*{(cos^2a/sin^2a-1)/ctga}=

=tga/{(cos^2a-sin^2a)/cos^2a}*{(cos^2a-sin^2a)/sin^2a}/ctga}=tga*cos^2a/cos2a*cos2a/{sin^2actga}=tga*ctg^2a*tga=1